TRAF6 controls T cell homeostasis by maintaining the equilibrium of MALT1 scaffolding and protease functions - O’Neill, Thomas J.; Gewies, Andreas; Seeholzer, Thomas; Krappmann, Daniel (Frontiers in Immunology, 2023)
MALT1 is a core component of the CARD11-BCL10-MALT1 (CBM) signalosome, in which it acts as a scaffold and a protease to bridge T cell receptor (TCR) ligation to immune activation. As a scaffold, MALT1 binds to TRAF6, and T cell-specific TRAF6 ablation or destruction of MALT1-TRAF6 interaction provokes activation of conventional T (Tconv) effector cells. In contrast, MALT1 protease activity controls the development and suppressive function of regulatory T (Treg) cells in a T cell-intrinsic manner. Thus, complete loss of TRAF6 or selective inactivation of MALT1 catalytic function in mice skews the immune system towards autoimmune inflammation, but distinct mechanisms are responsible for these immune disorders. Here we demonstrate that TRAF6 deletion or MALT1 paracaspase inactivation are highly interdependent to cause the distinct immune pathologies. We crossed mice with T cell-specific TRAF6 ablation (Traf6-deltaT) and mice with a mutation rendering the MALT1 paracaspase dead in T cells (Malt1 PD-T) to yield Traf6-deltaT;Malt1 PD-T double mutant mice. These mice reveal that the autoimmune inflammation caused by TRAF6-ablation relies strictly on the function of the MALT1 protease to drive the activation of Tconv cells. Vice versa, despite the complete loss of Treg cells in Traf6-deltaT;Malt1 PD-T double mutant mice, inactivation of the MALT1 protease is unable to cause autoinflammation, because the Tconv effector cells are not activated in the absence of TRAF6. Consequentially, combined MALT1 paracaspase inactivation and TRAF6 deficiency in T cells mirrors the immunodeficiency seen upon T cell-specific Malt1 ablation.